A Patient with Acute Myocardial Infarction who Experienced Mortality due to Ventricular Septal Rupture: A Case Report - Romi Ermawan (Cardiovascular and Cardiometabolic Journal, 2022)
Ventricular septal rupture (VSR) is one of the rare complications of acute myocardial infarction (AMI). Although the incidence decreased in percutaneous coronary intervention (PCI) era, the mortality rate remained extremely high. We report a case of an AMI patient who developed a post-fibrinolytic VSR, which was confirmed by echocardiography. Although rescue PCI had been performed, the clinical condition did not improve because he was also having coronary slow flow (CSF). Then he fell into cardiogenic shock and acute lung edema, and died. The main key to dealing with VSR is to reduce afterload so that the left-to-right bypass flow can be reduced in order to maintain the adequate LV stroke volume. In addition to pharmacological therapy, mechanical supportive therapy and correction of VSR both surgically or transcatheterly are required. However, AMI patients with VSR still have a poor prognosis even with the optimal treatment. Keywords: Acute myocardial infarction, Mortality, Ventricular Septal Rupture